2016
DOI: 10.3315/jdcr.2016.1226
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide induced acute generalized exanthematous pustulosis

Abstract: Introduction: Enzalutamide (Xtandi®) is a new potent inhibitor of the signaling pathway for the androgen receptor with a half-life of 5.8 days. It has been on the market for the treatment of metastatic castration-resistant prostate cancer since November 2013. Objective:We report the first case of acute generalized exanthematous pustulosis (AGEP) induced by enzalutamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Recently, the National Comprehensive Cancer Network (NCCN) guidelines were updated to recommend apalutamide or enzalutamide, another second-generation antiandrogen, in patients with nmCRPC with background ADT therapy [ 11 ]. Skin rash was not observed to be an adverse drug reaction (ADR) in Phase 3 trials, either in nmCRPC or mCRPC patients [ 12 , 13 ] with enzalutamide, although a case report of enzalutamide-induced acute generalized exanthematous pustulosis was recently reported and the USPI includes rash as an ADR observed in post-marketing [ 14 ]. Skin rash has also been reported with the first-generation oral non-steroidal antiandrogen drug bicalutamide and other new-generation oral antiandrogen drugs such as darolutamide [ 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the National Comprehensive Cancer Network (NCCN) guidelines were updated to recommend apalutamide or enzalutamide, another second-generation antiandrogen, in patients with nmCRPC with background ADT therapy [ 11 ]. Skin rash was not observed to be an adverse drug reaction (ADR) in Phase 3 trials, either in nmCRPC or mCRPC patients [ 12 , 13 ] with enzalutamide, although a case report of enzalutamide-induced acute generalized exanthematous pustulosis was recently reported and the USPI includes rash as an ADR observed in post-marketing [ 14 ]. Skin rash has also been reported with the first-generation oral non-steroidal antiandrogen drug bicalutamide and other new-generation oral antiandrogen drugs such as darolutamide [ 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We could only find two other cases of cutaneous adverse events to androgen receptor inhibitors in the English literature ( Table 1 ) ( 16 , 17 ). These two cases reported that skin lesions were noticed within two weeks after starting enzalutamide and were improved after hormone therapy.…”
Section: Discussionmentioning
confidence: 98%
“…[11] Skin rash was not observed to be an adverse drug reaction (ADR) in Phase 3 trials, either in nmCRPC or mCRPC patients [12,13] with enzalutamide, although a case report of enzalutamide-induced acute generalized exanthematous pustulosis was recently reported and the USPI includes rash as an ADR observed in post-marketing. [14] Skin rash has also been reported with the rst-generation oral non-steroidal antiandrogen drug bicalutamide and other new-generation oral antiandrogen drugs such as darolutamide. [15][16][17][18] It remains to be elucidated if skin rash is a class-effect, particularly in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%